Digital Literacy as Nonformal Learning: An Analysis of Information Technology Investment and UMKM Competencies in Aceh - Nurmalawati Nurmalawati; Safriatullah Safriatullah; Muhammad Ramadhan; Amrullah Amrullah (LaKaspia, 2026)
This study examines digital literacy as a form of nonformal learning through patterns of information technology investment among UMKM in Aceh. UMKM actors in Aceh continue to face fundamental challenges in mastering digital literacy, including limited digital competencies, inadequate technological infrastructure, and unequal access to digital learning opportunities. These conditions contribute to a persistent digital divide, which is further influenced by the limited role of educational institutions, including Islamic schools and community-based learning institutions, in preparing society for digital transformation. The study aims to explore information technology investment patterns among UMKM in Aceh as manifestations of nonformal learning processes, identify the role of technology-based training and mentoring in improving entrepreneurs’ digital competencies, and examine the potential contribution of educational institutions in supporting community digital transformation. This research employed a qualitative field research approach. Data were collected through in-depth interviews, participatory observation, and documentation studies involving 24 informants selected through purposive sampling in Banda Aceh, Aceh Besar, and Aceh Tengah. Data were analyzed inductively using thematic analysis, and findings were presented descriptively and interpretatively without making causal claims beyond the scope of qualitative inquiry. The findings reveal that 71% of informants experienced self-directed digital learning through gradual technology adoption, ranging from the use of WhatsApp Business to online marketplaces. UMKM actors who received structured technology training and mentoring demonstrated higher levels of digital competence and more significant business performance improvements compared to those relying solely on self-learning. The study concludes that technology adoption among UMKM in Aceh fundamentally represents a process of nonformal learning that requires systematic support from educational institutions and local governments through structured and sustainable digital literacy assistance programs